ANALISIS KESALAHAN FONOLOGI DIALEK ETNIS LAMPUNG DALAM MEMBACA Q.S AL-FATIHAH DAN AL-ZALZALAH - Yuni Lestari (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
Language becomes a unifier for a country, including Indonesia, which is a country with a variety of cultures, ethnicities and religions. Based on the fact that in Indonesia there are many languages ​​in each region, with different dialects or accents, Arabic which is one of the languages ​​studied in Indonesia, especially in the Lampung area, has differences in pronunciation and even phonological errors. The research method used in this study is a qualitative descriptive method. Data collection techniques were carried out by interview, observation, documentation and error analysis. Based on the research conducted, the results obtained are phonological errors in several Arabic consonant letters such as, , ذ becomes ز, غ becomes ر and “go”, ش becomes س, ص becomes س, the letter becomes , ز becomes ج, ح becomes ه, ث becomes س , ط becomes ت , and ل becomes لّ.